Pengaruh Green Accounting dan Ukuran Perusahaan terhadap Tax Avoidance dengan Profitabilitas sebagai Variabel Moderasi - Anita Achmad Payu; Anita Nursanti; Novianti Irwanto (Al-Buhuts, 2025)
This study aims to analyze the effect of green accounting and company size on tax avoidance with profitability as a moderating variable. The research population includes mining companies listed on the Indonesia Stock Exchange (IDX) during the period 2021–2023. This study uses a quantitative approach with Structural Equation Modeling (SEM) analysis techniques based on Partial Least Squares (PLS) processed using Smart PLS version 4.0 software. This method was chosen because it is capable of testing causal relationships between variables and the role of moderation simultaneously. The results show that green accounting has a positive and significant effect on tax avoidance, while company size has no significant effect on tax avoidance. In addition, profitability is proven to strengthen the effect of green accounting on tax avoidance, indicating that companies with high profitability tend to utilize green accounting practices as a legal tax management strategy. These findings provide empirical contributions by expanding the literature on the determinants of tax avoidance, particularly in the context of mining companies in Indonesia, and confirm the role of profitability as an important contextual factor in corporate tax management behavior.